2014
DOI: 10.1097/aog.0000000000000279
|View full text |Cite
|
Sign up to set email alerts
|

Receipt of Prescription Contraception by Commercially Insured Women With Chronic Medical Conditions

Abstract: Objective To assess differences in receipt of prescription contraception among women with and without chronic medical conditions. Methods This observational study used 3 years of administrative claims records for insured women aged 21–45 years who were enrolled in a commercial insurance company in Michigan between 2004 and 2009. Women were considered to have a chronic medical condition if they had at least two claims for one of the following conditions, in order of prevalence in our study population: hyperte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
43
3
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(49 citation statements)
references
References 27 publications
1
43
3
2
Order By: Relevance
“…20,22 Unlike our study, Perritt et al 20 found no association between heart disease and any contraception use in a representative Maryland sample of recent mothers. They also reported lower odds of contraception use at conception among women with prepregnancy hypertension compared with non-hypertensive women (odds ratio [OR] = 0.5; 95% CI: 0.3, 0.8) and lower odds for postpartum contraception use among women with prepregnancy diabetes compared to women without (OR = 0.5; 95% CI: 0.1, 0.9).…”
Section: Discussioncontrasting
confidence: 81%
See 2 more Smart Citations
“…20,22 Unlike our study, Perritt et al 20 found no association between heart disease and any contraception use in a representative Maryland sample of recent mothers. They also reported lower odds of contraception use at conception among women with prepregnancy hypertension compared with non-hypertensive women (odds ratio [OR] = 0.5; 95% CI: 0.3, 0.8) and lower odds for postpartum contraception use among women with prepregnancy diabetes compared to women without (OR = 0.5; 95% CI: 0.1, 0.9).…”
Section: Discussioncontrasting
confidence: 81%
“…We examined data among all women at risk of unintended pregnancy in the general population and not only among recent mothers. In another study that examined eight chronic medical conditions, 22 women with at least one chronic condition were less likely to receive prescription contraception than women who had no chronic condition (OR = 0.85; 95% CI: 0.76, 0.96). Notably, effect estimates for asthma and diabetes were comparable to ours and CVD was not assessed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lack of education, low socioeconomic status, reduced employment, limited access to health care, disrupted family dynamics, and intimate partner issues like violence, are a few outcomes noted among women who experience unplanned pregnancies (Brown & Eisenberg; Gipson et al; Sonfield et al). Health-related research has largely focused on physical and mental conditions that can precede unplanned pregnancy, for instance the influence of depression, stress, and chronic disease (CD) on sexual and contraceptive behaviors, rather than the health outcomes that follow it (Denobles et al, 2014; Chor, Rankin, Harwood, & Handler, 2011; Holing, Beyer, Brown, & Connell, 1998; Davis, Pack, Kritzer, Yoon, & Camus, 2008; Hall, Kusunoki, Gatny, & Barber, 2014; Hall, Moreau, Trussell & Barber, 2013; Hall, Reame, O’Connell, Rickert, & Westhoff, 2012; Chen, Stiffman, Cheng, & Dore, 1997; Steinberg et al, 2013). Some literature exists to describe unplanned pregnancy-related perinatal and postpartum depression (Cheng, Schwarz, Douglas, & Horon, 2009; CDC, 2007) and on whether induced abortion causes mental health (MH) morbidity (APA, 2008; Charles, Polis, Sridhara, & Blum, 2008; Steinberg & Finer, 2012; Steinberg & Finer, 2011; Foster, Steinberg, Roberts, Neuhaus, & Biggs, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…While common chronic disease and mental health conditions are recognized as leading causes of morbidity and mortality, their implications for women’s reproductive health (reproductive health) and family planning have been given less attention. A growing number of research studies have shown that chronic diseases, depression, anxiety, and stress are linked with decreased fertility, perinatal and infant morbidity, “risky” sexual and contraceptive behaviors, and increased rates of unintended pregnancy and sexually transmitted infections (Williams, March, & Rasgon, 2007; Grote et al, 2010; Adler et al, 2007; Denobles et al, 2014; Chor et al, 2011; Holing et al, 1998; Davis et al, 2008; Hall et al, 2014; Hall et al, 2013). Within current public health systems and policies, however, women’s general and mental health and healthcare needs have been largely marginalized from their reproductive health and family planning issues.…”
Section: Introductionmentioning
confidence: 99%